Characterizing pain in patients with Fabry disease: findings from a web-based cross-sectional survey in the US - Eric Wallace; Dawn Laney; Ibrahim Warsi; Connie Baldwin; Jack Johnson; Joseph Kupferman; Pronabesh DasMahapatra; Nicole Lyn (Orphanet Journal of Rare Diseases)
Abstract Background Fabry disease (FD) is a rare, progressive disorder caused by pathogenic variants of the GLA gene resulting in the accumulation of toxic metabolites. Pain is a hallmark of FD, and patients often present with heterogeneous pain profiles. This cross-sectional, web-based survey was conducted to characterize pain and pain crises in patients with FD in the United States and explore the effects of sex, disease phenotypes, and treatment on pain. Results A total of 66 participants (mean ± standard deviation [SD] age: 44.0 ± 12.7 years; females: 59.1%) completed the survey. Participants reported experiencing pain in upper (34.8%) and lower (43.9%) extremities several times a day and abdominal pain (31.8%) a few times a week. Overall, participants reported the nature of their pain as triggered (upper extremities: 47.0%; abdomen: 51.5%) or sudden (lower extremities: 57.6%). Female participants reported experiencing pain in upper (46.2%) and lower (48.7%) extremities several times a day and described it as sudden or triggered (48.7%) in upper extremities and sudden (61.5%) in lower extremities. Pain crises were reported in the lower extremities (80.0%), followed by the upper extremities (66.7%) and the abdomen (51.1%), and were often characterized as burning, tingling, or stabbing. A higher proportion of female participants (84.6%) than that of male participants (73.7%) reported pain crises in lower extremities. The duration of pain crises varied from 30 min to several days for different subgroups depending on sex and FD phenotypes. Most participants (81.0%) reported symptom improvement after 12 months of FD-specific treatment. Participants reported improvement in neuropathic symptoms (burning in hands, 45.9%), with an overall mean (± SD) satisfaction score of 7.2 (± 1.7) with agalsidase beta as the most recent medication. Conclusions Pain was largely reported to be triggered across all subgroups. Consistent pain profiles were noted in participants across sex and FD phenotypes. Female participants reported pain burden similar to that of male participants, and pain crisis experience was heterogeneous across the subgroups. Most participants reported improvement in symptoms after FD-specific treatment and a high treatment satisfaction score with agalsidase beta.